De La Mettrie's Ghost - Nunn, C. author. aut Link
VIII, 235 p.
Keywords: This book is about how we make choices. Drawing together evidence from 21st century chemistry to Victorian politics, enlightenment philosophy, Roman drama and beyond, it is a compelling hunt for the nature of free will.